Autumn Skies; A Bluebell Inn Romance - Hunter, Denise, 1968- (Thorndike, Maine : Center Point Large Print, 2021)
"The Bluebell Inn is turning a profit, and its time for the Bennett siblings to sell it and move on. Only Grace has plans to stay in the small lake town of Bluebell, North Carolina, where she hopes her growing outfitters business will save her from the loneliness of her siblings departure and the persistent sense of unworthiness in her life. A gunshot wound resurrects the past for Secret Service agent Wyatt Jennings, and a mandatory leave of absence lands him in Bluebell. There he must come to grips with the tragedy that altered his life fourteen years ago. When Wyatt books a room at the Bluebell Inn, sparks fly between him and Grace. She volunteers to be his mountain guide, and he soon opens up to her, drawn to her strength and sense of humor. But both are reticent to talk about the survivors guilt they each carry, and when their pasts finally collide, their budding romance might not survive the truth."--
Keywords: Hotelkeepers -- Fiction; Brothers and sisters -- Fiction; Life change events -- Fiction; Guilt -- Fiction; Man-woman relationships -- Fiction; North Carolina -- Fiction; Christian fiction; Fiction; Romance fiction; Romance fiction; Christian fiction